A smart flexible supercapacitor enabled by a transparent electrochromic electrode composed of W18O49 nanowires/rGO composite films. Issue 9 (9th February 2022) - Hassan, Muhammad; Abbas, Ghulam; Lu, Yao; Wang, Ziya; Peng, Zhengchun
Abstract : Benefitting from smart structural configuration, the W18 O49 NWs/rGO composite based smart supercapacitor achieved high capacitance properties, excellent stability, and high sustainability in optical modulation (96%) is promising for real applications. Abstract : In this study, we fabricated a transparent conductive electrode by co-assembly of Ag and W18 O49 nanowires, followed by the deposition of several W18 O49 NWs/rGO composite layers. The as-fabricated transparent electrode exhibits tunable transmittance (72–84% at 550 nm) and a conductivity of 23–39 Ω sq −1 . Noteworthily, the hybrid film structure made of 15 layers of W18 O49 NWs/rGO composite reveals an areal capacitance of 92 mF cm −2 with a fast and reversible switching response. The electrode can sustain an optical modulation of 94.7% even at a high current density of 10 mA cm −2 . Furthermore, the electrode exhibits excellent electrochromic performance with fast switching speeds (8 s for coloration and 8.45 s for bleaching), high colouration efficiency (46 cm 2 C −1 ) and remarkable stability (96.41% of the original optical modulation). A smart bifunctional electrochromic supercapacitor based on this electrode demonstrates a maximum areal capacitance of 48 mF cm −2 and an energy density of 5.2 μW h cm −2 with 0.391 mW cm −2 power density. The device shows excellent mechanical flexibility and stability over 4000 cycles of the charge/discharge test. The dual-functional supercapacitor with a rapid and reversible response and high sustainability in optical modulation (96%) even under high current charge/discharge conditions is promising for real applications.